Evaluated Acute and Repeated Dose 90-day Oral Toxicity Studies of Thanh nhiet - Nhuan trang Ba Giang Capsules - Hong, Tran Nguyen; Quynh Anh, Chu; Thi Lien, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2025)
Thanh Nhiet Ba Giang capsules (TNBG) for treament of mouth ulcers, skin rash, erythema, acne and fever were evaluated acute and repeated – dose toxicities in mice and rabbies, respectively. The acute toxicity carries out according to Behrens’s method result in the LD 50 of TNBG is greater than 92 capsules/kg body weight. In the repeated – dose toxicity study, rabbits were orally administrated TNBG with the dosage of 0,374 and 1,122 capsules/kg/day for 90 days. Blood samples were collected and analyzed hematological, biochemical parameters on experimental day 0, 15, 30, 60 and 90. The last day of experiment, liver and kidney were excised, tissues samples were paraffin-wax-embedded sections and stained with hematoxylin-eosins for histopathological exams. The hematological and serum biochemical values were no significant different between the control and treatment groups. Moreover, no damage in structrue of both liver and kidney were observed.